The Effect of Service Attributes, Attractiveness, and Excellence on Consumer Satisfaction at CV Eko Auto Service Workshop in Harjosari II Village, Sub-District Medan Amplas - Muhammad Wahyu; Muhammad Rahmat; Toni Hidayat; Rukmini Rukmini; Rido Mukti (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the Influence of Service Attributes, Power, Attraction and Excellence on Consumer Satisfaction at CV Eko Auto Service Workshop in Harjosari II Village, Medan Amplas District. In this study, the data collection technique used the random sampling method, the sample used was 65 respondents. All analyses in this study were assisted by the SPSS 25.0 program. The data analysis technique was carried out through classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the t-test that has been carried out, the results obtained were that the Sig. value of the Service Attribute variable was obtained at 0.001 <0.05 and the t count value (2.716)> t table (1.670). So it can be concluded that the Service Attribute variable has a positive and significant effect on the Consumer Satisfaction variable. Furthermore, the Sig. value of the Attractiveness variable obtained was 0.004 <0.05 and the t count value (3.154)> t table (1.670). So it can be concluded that the Attractiveness variable has a significant effect on the Consumer Satisfaction variable. Furthermore, the Sig. value of the Excellence variable obtained is 0.000 <0.05 which has a significant effect on the Consumer Satisfaction variable. From these data, the calculated t value is (10.882)> t table (1.670). So it can be stated that the Excellence variable has a positive and significant effect on the Consumer Satisfaction variable.